Analisis Bauran Pemasaran Pelayanan Kedokteran Olahraga pada Rumah Sakit Olahraga Nasional Berdasarkan Persepsi Pihak Manajemen Rumah Sakit dan Persepsi Atlet Sekolah Khusus Olahragawan (SKO) Ragunan - Bunga Listia Paramita; Wahyu Sulistiadi (Program Studi Magister Manajemen Rumah Sakit, Jenjang Pasca Sarjana (S2), Pasca Sarjana Universitas Muhammadiyah Yogyakarta, 2021)
In order to carry out marketing programs effectively, perceptions of the various elements of the marketing mix need to be heard from the hospital management and the patient. This study aims to analyze the marketing mix of sports medicine services at the National Sports Hospital (RSON) which is viewed from two sides, perception of the hospital management, and athlete’s perception represented by special sports school (SKO) Ragunan. This research is a descriptive study with a qualitative method approach using in-depth interview techniques, observing hospital marketing activities, reviewing hospital documents and conducting a questionnaire survey about perceptions of SKO Ragunan athletes which was conducted in October 2020. 40 of 133 questionnaire met the criteria for analysis. Most of the respondents had a positive perception (agreed) on the components and items of the marketing mix assessment at RSON with the highest assessment on the people skills / attitudes and the lowest on the aspect of promotion. The management confirmed the suitability of the survey results with the current hospital conditions. Coordination between hospital owners and leaders is required, as well as the evaluation of promotional media used so that marketing strategies, especially those related to promotional activities, can run optimally and on target.